Generation Of A Scenic Image By Tacking Multiple Images (International Journal of Engineering and Computer Science, 2017)
Image tacking is the process performed to generate one scenic image from a series of smaller, overlapping images. The quality of image stitching is measured by the similarity of the stitched image to each of the input images, and by the visibility of the cease between the stitched scenic images. Image processing techniques involved with treating the image as a two-dimensional signal and applying standard signal processing techniques to it. Image tacking presents different stages to render two or more overlapping images into a ceaseless stitched image. Scale Invariant Feature Transform (SIFT) algorithm is applied to perform the detection and matching control points step and  Random Sample Consensus (RANSAC) algorithm is a general parameter estimation approach designed to find the best matching points are used In this process .